THE INVESTIGATING THE STUDENTS USE OF ENGLISH INTERNET SLANG AT 4TH GRADE ENGLISH EDUCATION UIN MATARAM - Pusfita Hunaeda Mahfud; Hery Rahmat (Cordova Journal, 2024)
Internet slang is often used in informal communication. The purpose of this research is to find out what are the factors of students of 4th grade English Language and Education UIN Mataram in using internet slang, and students perceive toward the use of internet slang in communication. This research used qualitative case study method to obtain quantitative data, this research using 2 instruments which are questionnaires and interviews. The author distributed questionnaires to 53 respondents consisting of 4 classes, namely classes A, B, C, and D in collecting data. The results showed that more than half of the respondents said that there are 5 factors that influence them, which are; 1. Social status, 2. Age, 3. Social Distance of Familiarity, 4. Situations, and 5. Media and Popular Culture, next findings There are 3 students' perspectives about the internet slang, first is the desire to appear cool, second is facilitate communication, the last is conceal information from others. Another discovery is 32 respondents (60.37%) understand the term of internet and 17 respondents (32.08%) do not understand the term of slang, it can be concluded that students at 4th Grade Uin Mataram mostly understand the terms of Internet slang